Are these the accountable teacher subjects citizens want? - Skerritt, Craig (Education Policy Analysis Archives, 2022)
This paper represents an attempt to bring about more deliberation vis-à-vis the accountability so often called for by society. It is concerned with the impact of contemporary accountability on the subjectivities and identities of teachers and the production of accountable teacher subjects. In problematising accountability, the intention of this paper is not to provide concrete answers but to instigate more creative and critical thinking about and reflections on accountability. This paper sets out to highlight tensions, provoke readers, and generate questions—questions for policy and practice about the nature, value, purposes and effects of contemporary accountability. The issues discussed here are not simply teachers’ issues, however, but issues for us all, and collectively we must find solutions. We must ask questions about accountability and questions of accountability and consider how and why professionals are subjected to accountability and the ways in which accountability shapes subjectivity.